Risk of Posterior Capsular Rupture during Phacoemulsification in Patients with the History of Anti-VEGF Intravitreal Injections: Results from the Pan-American Collaborative Retina Study (PACORES) Group - Raul Velez-Montoya; Idaira Sanchez-Santos; Mauricio Galvan-Chavez; Lihteh Wu; J. Fernando Arevalo; María H. Berrocal; Arturo A. Alezzandrini; Marta S. Figueroa; Roberto Gallego-Pinazo; Rosa Dolz-Marco; Clara Martinez-Rubio; Roberto Gonzalez-Salinas (Journal of Ophthalmology)
Purpose. To assess the risk for capsular rupture during routine phacoemulsification in patients with a history of anti-VEGF injections and other possible risk modifiers such as treatment patterns, type of anti-VEGF agent, and experience of the surgeon, among others. Methods. This study reviewed the medical records of 11,129 patients from 7 different hospitals in 5 countries. The study included 939 patients that underwent routine phacoemulsification and had a history of anti-VEGF therapy. We excluded patients with known risk factors for capsular rupture, as well as patients with a history of other retinal procedures. The study extracted data regarding general demographics, the number of previous injections, type of anti-VEGF agent, details of cataract surgery, and anti-VEGF treatment patterns. Results. Overall prevalence of posterior capsular rupture: 7.45% (95% CI: 5.9–9.32%). The mean number of injections per patient was 3.37 ± 2.8. More than 50% of the patients received their last anti-VEGF injection within three months before cataract surgery. The complication rate during intravitreal injections was 1.07%. In the univariate analysis, the experience of the cataract surgeon (inexperience surgeons; OR: 2.93) and the history of prior anti-VEGF therapy (OR: 1.77) were significant risk indicators for PCR (p<0.05). However, after controlling for age in the multivariate analysis, the trend did not reach a statistical significance. Conclusion. The risk for capsular rupture is higher in patients with a history of intravitreal anti-VEGF injections.